The phenomenon of the precariat in the Polish labour market during Poland’s membership in the European Union - Cymbranowicz, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2019)
Studies of the scale of unemployment in Poland and in Europe conducted in recent years lead to the conclusion that one of the largest and growing problems of the modern labour market is the unemployment rate among young people. An unfavourable phenomenon related to this issue, which is increasingly often appearing in public debate, is the rising unemployment of graduates. Therefore, it is important to attempt to identify related phenomena in today’s job market, and one of such phenomena is the emergence of a new type of employee in the labour market, a member of the precarious class. The analysis aims to present the origins, nature and scale of the precariat phenomenon in Poland. The issue is described from the perspective of the labour market position of a selected social group, i.e. young people entering the labour market after finishing their education. The study attempted to identify factors that affect this phenomenon and the characteristics confirming the sense of its separateness in the labour market.